Perang Diponegoro sebagai Tendangan Bola Salju Kemerdekaan Indonesia - Suyanto, Hari; Wahid, M. Hasanuddin (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2023)
The Diponegoro War which lasted for five years from 1825-1830 was motivated by Prince Diponegoro's dislike of interfering too much with the internal affairs of the Yogyakarta Palace plus the Dutch action unilaterally fixing the land to be used by the railroad crossing the land of Prince Diponegoro's ancestral grave, this sparked anger until there was resistance to the Dutch Colonialism. The researcher was inspired by Ustadz Salim.A.Fillah's lectures, which often discussed the story of the Java War, especially the history of Prince Diponegoro, where if sequenced from Prince Diponegoro's resistance, stelsel fort , cultuur stelsel, ethical politics to the mobilization of students led by aristocrats who were literate in politics as a kick a snowball of the Indonesian national movement towards independence. This research aims that the nation's current historical experience has been largely forgotten by the millennial generation, and awareness of participating in defending the country is very low, therefore the researcher hopes that the continuity of the story of the Diponegoro war so that the national movement against colonialism can contribute to the awareness of defending the country for the next generation of the nation. Keywords: